Y STR Allele sizes - Bidon, Tobias; Janke, Axel; Fain, Steven R.; Eiken, Hans Geir; Hagen, Snorre B.; Saarma, Urmas; Hallström, Björn M.; Lecomte, Nicolas; Hailer, Frank (Dryad Digital Repository, 2014)
A table of allele sizes of 9 Y STR markers from 134 individuals